THE INFLUENCE OF THE APPLICATION OF SUSTAINABILITY ACCOUNTING PRINCIPLES IN CARRYING OUT ECOTOURISM ACTIVITIES IN COMPANIES IN BALI WITH THE CONCEPT OF TRI HITA KARANA - I Nyoman Sutapa; Ni Luh Putu Mita Miati; I Putu Gde Chandra Artha Aryasa (International Journal of Social Science, 2023)
Ecotourism management can be interpreted as an effort to optimize the use of natural and cultural resources responsibly and sustainably, with the aim of meeting the needs of tourists and also providing benefits to the local community and the environment. Ecotourism management covers various aspects, such as environmental management, financial management, human resource management, infrastructure management, and the development of programs and activities in accordance with ecotourism principles. In ecotourism management, collaboration between the government, community, and private sector is needed to achieve the goal of sustainable tourism developmentBali has great potential to improve the welfare of local communities and preserve the environment, but there are still some problems in its implementation in Bali. Several researchers have conducted research on ecotourism management. The population in this study was 2,945 with a total of 100 samples taken which were distributed to several locations in BALI. Data Analysis Method using Partial Least Square (PLS). The results of this study conclude that sustainability accounting has a positive effect on ecotourism management and sustainability accounting with the concept of tri hita karana has no effect on ecotourism management